DAMPAK SUPLEMENTASI PIL BESI SELENIUM TERHADAP STATUS HORMON TIROID DAN KADAR HEMOGLOBIN PADA WANITA USIA SUBUR DI DAERAH GONDOK ENDEMIK - Sukati Saidin; Dhuto Widagdo (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
The Effect of Combination of Iron and Selenium Supplementation on the Status of Thyroid Hormone and Haemoglobin Levels of Child Bearing Age Women In Endemic Goitre Area.Background: Iodine Deficiency Disorder (IDD) and Iron Deficiency Anemia (IDA) still considered as a public health problem in Indonesia. It is possible that some people in endemic goiter area not only suffering from IDD but also IDA, particulary among Childbearing Age Women (CBAW). Based on the national household survey (SKRT, 2001), it was reported that the prevalence of IDA among CBAW in Central Java, 22.4%, while in Cianjur District was 36.6%. Iron deficiency not only caused the decreament of hemoglobin value, but also decreased the Tyroxin (T4) and triiodotironin (T3) hormon syntesis. The trace element which has important role for iodine metabolism is selenium (Se). So far IDA and IDD control programme in Indonesia have been conducted separately, by means not integrated in strategy and not using combination of iron and selenium supplementation.Objectives: The main objectives of this study are to find out the possibilities of integrated solution of IDD and IDA. To determine the effect of combination iron and selenium supplementation to iodine status and Hb level of CBAW in the endemic goiter area.Methods: Study design was randomized control trial. The study was conducted in Cangkringan Subdistrict of Sleman District of D.I. Yogyakarta. A total of 96 CBAW were randomly assigned into 3 groups. Each group received different treatment, but before starting, all subjects were received pirantel for deworming. Group A (n=31) received 400 mg of iodine (2 capsules) + ferrosulfate (60 mg elemental iron + 0.25 mg of folic acid) + 420 ug of selenium (yeast selenium); group B (n=31) received 400 mg of iodine + ferrosulfate and group C (n = 34) received 400 mg of iodine only (control group). Two capsules of iodine were given once in the beginning of study to all subjects, while ferrosulfate and selenium were given twice a week for 16 weeks. Data of hormon thyroxin (serum T4) and Hb was collected before and after intervention. Data of socialeconomi and selenium were collected at the first of study.Results: It was revealed that before treatment there were no significant difference of the average of Hb levels and the median value of serum T4 amongs 3 groups of study (p> 0.05). After 16 weeks intervention there were thyroid hormone status improvement (serum T4) to all groups as follows: group A (100%), group B (80%) and group C (66.7%) respectively.Conclusions: After 16 weeks intervention of iron and selenium preparate to CBAW who had received iodine supplementation, was able to improve status of thyroid hormone (serum T4) higher than to those who received iodine only (33.3%). The increment of Hb levels of CBAW who received iron and selenium supplementation (group A) was lower than those who received iron only (group B).Keywords: Childbearing Age Women, IDD, IDA, anemia and selenium.